2015
DOI: 10.1111/jpi.12270
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin decreases breast cancer metastasis by modulating Rho‐associated kinase protein‐1 expression

Abstract: The occurrence of metastasis, an important breast cancer prognostic factor, depends on cell migration/invasion mechanisms, which can be controlled by regulatory and effector molecules such as Rho-associated kinase protein (ROCK-1). Increased expression of this protein promotes tumor growth and metastasis, which can be restricted by ROCK-1 inhibitors. Melatonin has shown oncostatic, antimetastatic, and anti-angiogenic effects and can modulate ROCK-1 expression. Metastatic and nonmetastatic breast cancer cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
107
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 49 publications
11
107
1
1
Order By: Relevance
“…This result was consistent with a previous study (28). Nevertheless, the mechanisms by which the inhibitory effect of melatonin is prolonged were not investigated.…”
Section: Melatonin Induces Kiss1 Expression Via Gata3supporting
confidence: 82%
See 3 more Smart Citations
“…This result was consistent with a previous study (28). Nevertheless, the mechanisms by which the inhibitory effect of melatonin is prolonged were not investigated.…”
Section: Melatonin Induces Kiss1 Expression Via Gata3supporting
confidence: 82%
“…However, previous studies have demonstrated that melatonin inhibited the metastatic abilities of MDA-MB-231 breast cancer cells by inhibiting either Rho-associated protein kinase 1 or p38 mitogen-activated protein kinases (31,32,46). Likewise, the results of the present study revealed that melatonin inhibited the invasiveness of triple-negative breast cancer cells with no effect on proliferation.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Suppressing ROCK2 expression reduces high-glucose-induced hyperpermeability in renal glomerular endothelia [18]. Previous studies also have shown that melatonin modulates ROCK1 and ROCK2 activation to inhibit cancer cell progression [19,20]. Yet, the relationship between melatonin and ROCK activation in diabetic nephropathy remains unknown.…”
Section: Introductionmentioning
confidence: 97%